Actualization of information by euphemisms in legal texts - Bulakh , Maiia (Current issues of Ukrainian linguistics: theory and practice, 2019)
The paper focuses on the analysis of the euphemistic process in Ukrainian legal discourse. It is generally known that the reader is already accustomed to actively using euphemisms in political speeches, speeches by politicians and officials, where they become a part of manipulative tactics. The use of euphemisms in such texts is also relevant, since the specifics of its communication are excessive courtesy, mitigation of statements, and excessiveness of etiquette formulas. Moreover, the specificity of public broadcasting requires figurativeness, which is reflected both in the mitigation of the expression and in the deliberate exaggeration, roughness, that called dysphemization. The article aims to explore the euphemistic mechanisms in Ukrainian legal texts. To solve this problem this paper presents different approaches to the definition of the phenomenon of euphemism. The materials for the study were chosen texts of annual reports of Kyiv city state administration for 2015-2017 years and Strategy of Kyiv development till 2025. This material allows us to investigate the functions of euphemistic means in the texts of official legal documents, which the main implicit function is the ideological impact on citizens. Focusing on positive achievements in the report, at the same time, it is necessary to reflect the existing actual state of affairs. Euphemisms allow speaker to do, as much as possible, soften the statement, conceal the negative effects of action. However, traditionally hidden things such as social inequality, poverty, illness, age restrictions etc. are veiled. It will be shown that this is obligatory and typical characteristic of political discourse. The author points out the motivation of creating euphemisms in the political discourse and communicative potential of euphemistic units. In particular, the following approaches are mentioned in the studies of the motivation of the creation of euphemisms: euphemism as part of the demobilization strategy and euphemism as a component of the method of emotional contamination, that is, the suggestive verbal technique used to create the mood desired by the audience. The author examines in detail various ways of euphemistic mechanisms due to its linguistic peculiarities, such as euphemisms as metaphorical nominations, euphemism-terms, euphemisms with a negative epithet, syntactic euphemistic substitutions, as well as a specific information delivery structure known as contrast-based manipulation and generalization.
Keywords: euphemism, functions of language, mitigation, manipulative influence, legal texts.